COMPARISON OF LOCAL ADMINISTRATION OF AMINOPHYLLINE VERSUS NORMAL SALINE ON TRANSURETERAL LITHOTRIPSY IN PATIENTS PRESENTING WITH ACUTE RENAL COLIC - Khan, Hasham; Mustafa, Ghulam; Butt, Saqib; Nisa, Noor-Un; Haque, Ehsan-Ul- (Journal of University Medical & Dental College, 2020)
ABSTRACT BACKGROUND & OBJECTIVE: Acute renal colic is most common disease presented with agonizing pain worldwide. Our study aims to compare outcomes (mean operative time and frequency of complete stone removal) between local administrations of aminophylline versus saline on Transureteral lithotripsy (TUL) in patients presented with acute renal colic. METHODOLOGY: Our study design was randomized clinical trial, conducted at department of Urology & Kidney in Pakistan Institute of Medical Sciences, Islamabad. Study duration was 6 months (February 2017-July 2017). Ethical approval and consent forms were taken in our study. A sample size of 90 cases was calculated (1:1 randomization that is 45 patients in each group) using WHO calculator. Acute renal colic patients were selected through consecutive (non-probability) sampling. A random division of patients is done in two groups; Group-A underwent local administration of aminophylline and group-B patients were given placebo. SPSS version 24 was used for analysis purpose. Post stratification chi-square and t-test was utilized in analysis for comparisons. In our study, p-value≤0.05 was found significant. RESULTS: Total 90 cases were included in study. Mean age of patients was 47.56±18.1SD.Mean operative time was found to be significantly lower in Group-A (aminophylline group) as compared to group-B (placebo group) p=0.000. Group-A patients showed significantly high stone removal frequency as compared to group-B (44.4% vs 35.6%, p=0.03). CONCLUSION: Aminophylline is an effective and safe drug in terms of lower operative time and complete stone removal among acute renal colic patients undergoing transureteral lithotripsy.